Letter from R.E. Preston to James Curtis Booth, February 4, 1879 - Preston, Robert E., 1836–1911 (1879)
Robert E. Preston (1836–1911) asks for James Curtis Booth (1810-1888) to support him in his candidacy for Director of the Mint.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; United States. Department of the Treasury; Preston, Robert E., 1836–1911